The main legislative approaches to the criminalization of aggression (International relations and international law Journal, 2016)
In 1945, there emerged the issue of recognizing wars of aggression as a crime under international law. Ever since, the crime of aggression was integrated in many countries’ criminal laws. The article sets out the main legislative approaches towards formulating the elements of the crime of aggression, and towards the perspectives of criminal prosecutions for this crime in connection with the adoption, in 2010, of relevant amendments to the Rome Statute of the International Criminal Court. On condition of achievement of the number of ratifications necessary for the adoption of amendments to the Rome Statute of the International Criminal Court, there is a high probability, that the states most influential in the military, political, economic and ideological relation, will remain away from process of international legal criminalization of aggression. Most likely, they will interfere with activity of the International Criminal Court.
Keywords: International Criminal Court; crime of aggression; the Rome Statute; the Nuremberg International Military Tribunal; the Tokyo Interna-tional Military Tribunal; territorial integrity; political independence; Charter of the United Nations